Frequency dielectric response of ferroelectric–magnetic ceramic composites like PbZr0.65Ti0.35O3–BaFe12O19. Issue 5 (June 2015) - Guerra, J.D.S.; McIntosh, R.; M׳Peko, J.-C.; Hernandes, A.C.; Guo, R.; Bhalla, A.S.
Abstract: The dielectric properties of PbZr0.65 Ti0.35 O3 –BaFe12 O19 (PZT–BaM) multiferroic ceramic composites, obtained from the conventional solid-state reaction method, have been investigated. While there is some dielectric dispersion at low frequencies, the highly-stable values of dielectric permittivity over a wide frequency range, together with low dielectric losses (~10 −3 ), make these composites suitable for practical radio-frequency and potential microwave device applications. Toward high frequencies, the data reveal an anomalous resonance-like phenomenon. This resonance phenomenon is connected to an over-damped resonance mechanism for the vibration of the boundaries of polar regions, associated with the ferroelectric phase. A noticeable dependence of the parameters characterizing this last dielectric dispersion with the BaM concentration is found, indicating a strong influence of the magnetic phase on the dynamics of the ferroelectric domain-wall motion.